Assessment of seasonal and spatial variations in the nutritional content of six edible marine bivalve species by the response of a set of integrated biomarkers - Silva, Daniela (2021)
Bivalves are widely distributed through diverse habitats, including estuaries and coastal lagoons which are extremely productive ecosystems, and play important roles in trophic webs and in ecosystems’ biological processes. Bivalves, as well as other marine resources, have been a part of the humans’ diet since mankind started fishing. These resources have high nutritional values, being constituted by high protein and low fat contents, and its consumption is associated with several health benefits. Marine resources, like bivalves, that are highly appreciated by humans, represent an important economic value, being under pressure due to an increasing demand. Thus, it is important a sustainable and balanced exploitation of these resources, based on the knowledge of the biochemical composition of the aquatic species to comprehend its’ potential and nutritional value. The present study was conducted in Portugal, a country that has one of the highest consumptions of seafood in the world. Six commercially valuable species of marine bivalves were harvested in two distinct areas, Mondego estuary and Ria Formosa lagoon, and in two seasons, winter 2016 and summer 2017. The aims of the study were to: 1) determine the biochemical composition of each species in terms of total protein content, fatty acid and carbohydrate profiles; 2) identify potential spatial and seasonal variations between bivalve species sampled in each study area and season; 3) assess feeding behaviour of the bivalve species in both seasons and study areas. The results indicated diverse biochemical composition among bivalve species, with total protein as the major component, followed by fatty acid content, particularly by the essential fatty acids DHA and EPA, and glycogen and glucose as the main polysaccharide and monosaccharide, respectively, found in all specimens. In general, all species demonstrated a tendency for omnivory, with only S. marginatus presenting a clear herbivorous behaviour in summer. Despite M. galloprovincialis and R. decussatus showed the highest nutritional value in the Mondego estuary, in both seasons, it was more noticeable in winter. In Ria Formosa, C. edule and R. decussatus showed the highest nutritious value in both seasons, while C. gigas showed higher nutritive value in summer.